"O dinheiro do Otacílio" : indícios das relações entre agentes políticos, clubes de futebol e sujeitos de imprensa na modernidade desconfiada da Belo Horizonte dos anos 1940 - Ives Teixeira Souza (2022)
The objective of this research is to argue about the characterization of a distrustful modernity for Belo Horizonte city from the indications of the relationship between football clubs, political agents and press journalists that composed the city in the 1940s. Therefore, it makes use of the metaphor "Otacilio’s Money" to report on these clues from fragments of journalistic textualities of available digitally printed journals. During the fiftieth anniversary of Belo Horizonte, tensions between the voices of Minas in favor of the city’s modernities were evidenced, especially, with the democratic recovery after the end of the Estado Novo regime, when deputies, governor, councilors, deputy mayor and the mayor Otacílio Negrão de Lima were elected - many with close relations to football clubs and the media. This research does not just intend to enumerate the subjects, but, from the constant entanglement of the present modernities - soccer, press and municipality - proposes to argue about a Belo Horizonte characteristic: its distrustful modernity.